Contrasts in Moral Reasoning Capacity: The Fijians and the Singaporeans - Wimalasiri, Jayantha S. (Journal of business ethics, 2004)
The moral reasoning capacity of managementstudents in Fiji and in Singapore, twoculturally distinct nations, was examinedusing the Defining Issue Test (DIT). Statistical analyses of the data revealed amarked difference in the reasoning capacity of thetwo groups. In the Fiji sample, religion andrace were found to have a moderating effect onmoral judgment. In the Singapore sample, age,race and religion were found to have asignificant correlation with moral judgment. The data were subjected to paired-samplest-tests using p-score as a dependent variable. The results showed significant differences onthe p-score, recording a comparatively weakerreasoning capacity among the Fiji subjects. Theresults overwhelmingly confirms the assumptionthat culture plays a definite role indetermining one's moral judgment over andabove other variables. The implications offindings for cross-cultural management arediscussed.